PARSING POLYPHYLETIC PUERARIA : DELIMITING DISTINCT EVOLUTIONARY LINEAGES THROUGH PHYLOGENY - Cagle, William (East Carolina University, 2013)
A taxon is defined as polyphyletic when it does not include the last common ancestor of all true members of the taxon, resulting in a number of subgroups not united by a common ancestor. Previous work has suggested Pueraria (Fabaceae) to be polyphyletic. Although several taxonomic treatments have recognized Pueraria as an unnatural grouping since its creation in 1825, and two have put forth taxonomic hypotheses, the polyphyly has never been resolved. The need for further biosystematic research has always been cited as the reason no changes were proposed. This project attempted to address this issue by sampling broadly across phaseoloid legumes with an initial target goal of 156 species including 15 species of Pueraria. Ultimately, 104 species across 69 genera were sampled for AS2 and 116 species across 64 genera for matK. Phylogeny reconstruction was carried out using maximum likelihood and Bayesian inference. Both analyses yielded congruent tree topologies and similar support values. Both previous taxonomic hypotheses show some congruence with the data, but discrepancies do occur. This work provides strong support for the existence of five separate clades within the genus Pueraria, requiring the resurrection of the genus Neustanthus for P. phaseoloides along with the need to create a new genus each for P. stricta, P. peduncularis, and P. wallichii.
Keywords: Plant biology; Genetics; Phylogenetics; Polyphly; Biology, Genetics; Cladistic analysis; Biology--Classification; Pueraria